A lens on deaf identities - Leigh, Irene (New York ; Oxford : Oxford University Press, 2010)
This title explores identity formation in deaf persons. It looks at the major influences on deaf identity, including the relatively recent formal recognition of a deaf culture, the different internalized models of disability and deafness, and the appearance of deaf identity theories in the psychological literature.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Deafness; Identity (Psychology); Deafness -- Psychological aspects; Self-perception.; Group identity